Study on the control of chemical hazardous to health used in laboratories at Pusat Pengajian Sains Perubatan (PPSP), Universiti Sains Malaysia Kubang Kerian - Mustapa, Erma (Universiti Sains Malaysia, 2012)
This study was conducted to assess the risks that associated with control of chemical hazardous to health used in medical laboratories at Pusat Pengajian Sains Perubatan (PPSP) Universiti Sains Malaysia, Kubang Kerian. Most of the PPSP laboratories contain more hundreds of chemical hazardous to health that used for laboratory work and also for research. A part from the medical laboratory, the chemical are used by the student and laboratory workers and categorized as chemical hazardous to health along with other chemicals less hazardous to health during their research project and thenwork. The study is based on the observations of workers, researcher, and students to conduct research in PPSP laboratories. The primary parameters are used to analyze the risks including exposure of chemicals, hazard and risk levels. The method used in this study is based on the Occupational Safety and Health Act (OSHA). This study found that laboratory workers, researchers and students may be exposed to harmful of health risks arising from the effects of chemical hazardous to health, lack of knowledge in the use of material safety data sheet (MSDS) and personal protective equipment (PPE).